THE RELATIONSHIP BETWEEN HYBRID LEARNING DURING THE COVID-19 PANDEMIC AND ANXIETY LEVELS - IRFAN, MUFLIH NAUFAL (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT COVID-19 is a virus that quickly spread worldwide and made the government limit all social activities, including in the field of education. This is something that is new to all individuals and is prone to having an impact on their psyche. Therefore, this research is important. This study aims to find out how far the relationship between hybrid learning and anxiety levels during the COVID-19 pandemic in students at MA Citra Cendekia, South Jakarta. This type of research uses quantitative methods. The object of the research is class 10th and 11th students at MA Citra Cendekia, South Jakarta. The data in this study were collected using a questionnaire technique. The results showed that out of 54 samples, 20 people or 37.0% of them experienced anxiety caused by hybrid learning. There is a significant relationship between the two variables that impact students' cognition according to the statistical test results where the probability value is 0.008. COVID-19 merupakan virus yang menyebar dengan cepat ke seluruh dunia dan membuat pemerintah membatasi segala kegiatan sosial, tak terkecuali pada bidang pendidikan. Hal ini merupakan sesuatu yang baru bagi semua individu dan rentan berdampak pada kejiwaan mereka. Oleh karena itu, penelitian ini menjadi penting. Penelitian ini bertujuan untuk mengetahui sejauh mana hubungan antara pembelajaran hybrid (pembelajaran jarak jauh dan pembelajaran tatap muka) dengan tingkat kecemasan pada masa pandemi COVID-19 pada peserta didik di MA Citra Cendekia, Jakarta Selatan. Jenis penelitian ini menggunakan metode kuantitatif. Objek penelitian adalah peserta didik kelas X dan di MA Citra Cendekia, Jakarta Selatan. Data dalam penelitian ini dikumpulkan dengan menggunakan teknik angket. Hasil penelitian menunjukkan bahwa dari 54 sampel, sebanyak 20 orang atau 37,0% mengalami kecemasan yang disebabkan oleh pembelajaran hybrid. Terdapat hubungan yang signifikan antara kedua variabel tersebut yang berdampak pada kognisi peserta didik menurut hasil uji statistik dimana nilai probabilitasnya sebesar 0,008.